Karakteristik Campuran Beton Aspal (AC-WC) Dengan Pencampuran Minyak Solar Terhadap Parameter Marshall - Endra (Universitas Iskandar Muda, 2022)
Asphalt concrete used for road pavement consists of several types, namely: foundation layer, first wear layer, and second wear layer. Petroleum materials contained in the AC-WC asphalt concrete mixture can affect the stability of the mixed pavement, such as diesel oil. The purpose of this study was to determine how the effect of the diesel content contained in the laston mixture on the road surface layer. The test method is in the form of testing the Marshall characteristics using the Indonesian National Standard (SNI) and Bina Marga 2018. The Marshall test show that for variations in the ideal asphalt content for the test object with the number of collisions 2 x 75, the stability, flow, density, VIM values ??are obtained. , VMA, VFB, and Marshall Quotient (MQ) the percentage of diesel spraying was 0%, 1.5%, 2.5%, 3.5%, and 4.5% and the total number of specimens was 30 specimens. The results of the Marshall characteristic performance test on the lastton mixture with diesel oil content of 0%, 1.5%, 2.5% still meet the specifications, whereas the variation of 3.5%, and 4.5% do not meet the specification requirements. The diesel content contained has a bad influence on the asphalt concrete surface layer.